If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -3) = 46 Reorder the terms: 7(-3 + x) = 46 (-3 * 7 + x * 7) = 46 (-21 + 7x) = 46 Solving -21 + 7x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 7x = 46 + 21 Combine like terms: -21 + 21 = 0 0 + 7x = 46 + 21 7x = 46 + 21 Combine like terms: 46 + 21 = 67 7x = 67 Divide each side by '7'. x = 9.571428571 Simplifying x = 9.571428571
| 352-123=h | | 5x^2+8t-35=0 | | 8-4(-4r-3)=116 | | 5y-7=15x | | 4x+6-3x=11 | | 12w-4w=8 | | 3y-5x=-8 | | 26-3v=3(v-6) | | -4(m+9)=-128 | | T=3s+3.72 | | 0.4c+0.64c-1.06c=0 | | y+x+y-x=2x | | 3x-10-x=-14 | | -7(-4-2x)-4=94 | | 0.44c+0.07c=4.57 | | 18-4n=2x+10 | | 3(x+12)=6 | | -5(6m+5)=-25-3m | | 8x+11+3x=13-7x+4 | | 4h-I+3h-5i+h= | | -12(x+3)+4(4x-3)=3(x-6)+14 | | 16=4w+9 | | -11+5n=-91 | | 5(-7b-7)= | | X-10=2x+4 | | d-14.25=23.5 | | 8+3b=-1+3(3+b) | | 3/4-1+1/2x=3/8x+1/4 | | 2x-3+x=3x+1 | | -3(x-1)=2x+48 | | 5(x-7)+x=6(x-7)+7 | | x^2-16x=.35 |